Neolasioptera ramicola, a new species of Cecidomyiidae (Diptera) associated with Physalis angulata (Solanaceae) - Maia, Valéria Cid; Zart, Marcelo; Botton, Marcos [UNESP] (Sociedade Brasileira de Entomologia, 2009)
Neolasioptera ramicola Maia, uma nova espécie de Cecidomyiidae (Diptera) que induz galhas caulinares em Physalis angulata (Solanaceae) é descrita e ilustrada (larva, pupa, male, fêmea e galha) com base em material coletado em Bento Gonçalves, Rio Grande do Sul, Brasil.

Neolasioptera ramicola Maia, a new species of Cecidomyiidae (Diptera) that induces stem galls on Physalis angulata (Solanaceae) is described and illustrated (larva, pupa, male, female and gall) based on material from Bento Gonçalves, Rio Grande do Sul, Brazil.
Neolasioptera ramicola, uma nova espécie de Cecidomyiidae (Diptera) associada com Physalis angulata (Solanaceae)
Keywords: Physalis; Solanaceae; sul do Brasil; Physalis; Solanaceae; southern Brazil